2008
DOI: 10.3325/cmj.2008.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Nurses and Physicians in Terms of Organizational Culture: Who Is Responsible for Subordination of Nurses?

Abstract: Aim To investigate how nurses and physicians perceive organizational culture, their integration into the organizational processes, and relations within a health care team.Methods We performed a cross-sectional study that included 106 physicians and 558 nurses from 14 Slovenian hospitals in December 2005. The hospitals were randomly selected. We distributed the questionnaires on the same day to physicians and nurses during a morning shift. The total number of distributed questionnaires represented a 20% of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 25 publications
2
14
1
Order By: Relevance
“…Ovijač et al [9] established in an extensive study among doctors and nursing professionals that only 12% of (nursing) health technicians and 4% of nurses feel that doctors respect the nursing profession. In the study Skela-Savič and Pagon [10], nurses also expressed a sense of subordination to doctors; control orientation in Slovene hospitals correlates positively with the subordination of nurses and negatively with personal integration in an organization. Also, Skela-Savič et al [1] discovered in their research on successful leadership in Slovene hospitals that leaders from the field of medicine are the worst at performing their leadership role when compared to other personnel categories included in the study (doctors, nurses and non-health care workers).…”
Section: Introductionmentioning
confidence: 93%
“…Ovijač et al [9] established in an extensive study among doctors and nursing professionals that only 12% of (nursing) health technicians and 4% of nurses feel that doctors respect the nursing profession. In the study Skela-Savič and Pagon [10], nurses also expressed a sense of subordination to doctors; control orientation in Slovene hospitals correlates positively with the subordination of nurses and negatively with personal integration in an organization. Also, Skela-Savič et al [1] discovered in their research on successful leadership in Slovene hospitals that leaders from the field of medicine are the worst at performing their leadership role when compared to other personnel categories included in the study (doctors, nurses and non-health care workers).…”
Section: Introductionmentioning
confidence: 93%
“…Previous research conducted in Slovenian hospitals has shown that health-care practices have not been managed, implemented or controlled adequately [12], and that they have been founded on a culture and tradition of hierarchical hospital leadership [13]. Conversely, successful change implementation in Slovenian hospitals is mostly the result of teamwork, a form of work not supported or encouraged by the existing hierarchical organizational culture [14,15]. Importantly for the development of middle management, the role and inclusion of middle-level employees has been found to be extremely poor, which represents a great challenge for the top and middle management: they must find a way to tap into the potential of each employee, to meet organizational goals [15].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, successful change implementation in Slovenian hospitals is mostly the result of teamwork, a form of work not supported or encouraged by the existing hierarchical organizational culture [14,15]. Importantly for the development of middle management, the role and inclusion of middle-level employees has been found to be extremely poor, which represents a great challenge for the top and middle management: they must find a way to tap into the potential of each employee, to meet organizational goals [15]. Quality policy in health-care organizations is not defined clearly enough, making its transfer to lower organizational levels insufficient; this is where leadership and training should play a more significant role [12].…”
Section: Introductionmentioning
confidence: 99%
“…The scarcity of information about assessment of communication between occupational nurses and physicians obstructs references to other studies which concern health care service in general rather than its occupational health-related part. The issues of collaboration, communication problems, communication deficit as well as importance of good communication were noticed in other surveys proving that there was a field for action not only in Polish occupational medicine but in health care systems in general [4,11,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Shortell et al claim that for providing good health care to patients, the cooperation with all members of a team is necessary and physicians cannot be the only individuals responsible for patients [3]. Savic and Pagon claim that good cooperation between nurses and physicians is "of strategic importance for high quality patient care" and for "positive work environment for both groups of health professionals" [4]. Taking into account that those professionals, who are the main stakeholders in the Polish occupational health system, work together for the benefit of their patients (i.e.…”
Section: Introductionmentioning
confidence: 99%